Introduction - Costa, Ana (2011)
As the end result of a multidisciplinary investigation project conducted in Africa, this publication about Poverty and Peace in the Portuguese-speaking African Countries1 has the purpose, on one hand, of presenting the main conclusions of the studies conducted in these countries and, on the other, to provide a collection of guidelines for future research relevant to the comprehension of the combination of both phenomena.